Điều chế nano -MnO2 theo phương pháp phản ứng pha rắn giữa KMnO4 và Mn(CH3COO)2.4H2O có mặt NaCl làm chất phân tán - Trung và cộng sự, Bùi (Vietnam Journal of Chemistry, 2014)
Single-crystal a-MnO2 nanoneedles have been synthesized by a solid state reaction of KMnO4 and Mn(CH3COO)2.4H2O at room temperature with sodium chloride salt as a dispersant. The main manganese oxidation state, crystal structure and morphology of the synthesized products were examined by chemical ananlysis, XRD, SEM, TEM, …methods. The results show that a-MnO2 nanoneedles with diameters of 10 -20 nm and lengths of a few hundred nanometers were prepared in high yeild (> 95%). Mean SBET of 162 m2/g was achieved for the a-MnO2 products. It has also established that the existence of crystalline NaCl as a dispersant was the important factor effecting to the growth of a-MnO2 crystals.